Making Media Matter Critical Literacy, Popular Culture, and Creative Production - Thevenin, Benjamin (Taylor & Francis, 2022)
This book is an essential resource for media educators working to promote critical thinking, creativity, and civic engagement through their teaching. Connecting theory and research with creative projects and analyses of pop culture, it models an integrated and practical approach to media education. In order to prepare learners to successfully navigate rapid shifts in digital technology and popular culture, media educators in both secondary and university settings need to develop fresh, innovative approaches. Integrating concepts and practices from the fields of media studies, media arts, and media literacy, this book prepares teachers to help their students make connections between their studies, uses of media, creative expression, and political participation. As educators implement the strategies in this book in their curricula and pedagogy, they will be empowered to help their students more thoughtfully engage with media culture and use their intelligence and imagination to address pressing challenges facing our world today. Making Media Matter is an engaging and accessible read for educators and scholars in the areas of media literacy, media and cultural studies, media arts, and communication studies.